2017
DOI: 10.1159/000480139
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Study of Autoimmune Hepatitis Cases That Were Difficult to Differentiate from Drug-Induced Liver Injury

Abstract: Aim: Acute-onset autoimmune hepatitis (AIH) histopathologically presents with features of acute hepatitis and lacks a specific diagnostic method. Also, AIH is often difficult to differentiate from drug-induced liver injury (DILI). We aimed to investigate the final clinical diagnosis of these cases, and compare the clinical, biochemical, and histological characteristics of AIH vs. DILI. Methods: We examined the Digestive Disease Week Japan 2004 (DDW-J) scale scores, AIH scores, clinical data, and pathological f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…In addition, there was a tendency, albeit not significant, towards a higher frequency of eosinophils in AIH patients. Both of those findings are in line with previous data . However, regarding the type and intensity of cellular infiltrates and of cholestasis no other distinguishing feature was found that could have helped to accurately direct diagnosis towards DILI or AIH.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, there was a tendency, albeit not significant, towards a higher frequency of eosinophils in AIH patients. Both of those findings are in line with previous data . However, regarding the type and intensity of cellular infiltrates and of cholestasis no other distinguishing feature was found that could have helped to accurately direct diagnosis towards DILI or AIH.…”
Section: Discussionsupporting
confidence: 90%
“…It is conceivable that the more severe feature of cobblestone appearance of hepatocytes could be a characteristic of AP-AIH and thus useful for distinguishing from DILI, which has also been noted in previous studies. 43,52 In a study that compared AIH with DILI, Suzuki et al noted that the main findings of chronic hepatitis pattern, interface hepatitis, portal inflammation, and focal necrosis were present in all of their evaluated cases, although more severe in AIH. 17 Similar results were obtained in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…However, a new diagnostic scale to facilitate the diagnosis of DILI in Japan, the Digestive Disease Week Japan 2004 (DDW‐J) scale, which is highly sensitive and specific, was developed by modifying the Council for International Organizations of Medical Sciences/the Roussel Uclaf Causality Assessment Method (CIOMS/RUCAM) scale . Recently, Akemi Tsutsui et al . demonstrated that the DDW‐J scale was useful for differentiating AIH from DILI in cases with a DDW‐J scale score of ≥5 in 20 patients in whom it was difficult to differentiate autoimmune liver disease from DILI.…”
Section: Discussionmentioning
confidence: 99%